Integrating Edutourism and Epistemic Learning Patterns in Science Modules: A Strategy to Enhance Students’ Ecological Awareness - Raden Didi Kuswara; Ahmad Fadli; Marham Jupri Hadi; Sahratullah Sahratullah; Wirentake Wirentake; Naif Mastoor Alsulami (Jurnal Pendidikan MIPA, 2026)
Education is a key factor in tackling climate change, and educational tourism (edutourism) is a new approach to environmental education with supporting teaching materials. This research aims to develop and evaluate the effectiveness of a science module on educational tourism, integrated with environmental education, for enhancing students’ ecological awareness. The module was designed using the 4D development model (define, design, develop, and disseminate) within an ELP approach. Validation by 10 experts, including experts in learning, environmental, and educational tourism, as well as research instruments, confirmed that the module and instrument were suitable for use. The implementation phase tested module effectiveness using a quasi-experimental design with a non-equivalent control group across three meetings, including field observations, presentations of observational results, and the design of simple solutions to environmental problems. A total of 75 students from 3 secondary schools participated in this study, with 43 in the experimental group and 33 in the control group. Descriptive analysis indicated an increase in ecological awareness in both groups, with a larger increase in the experimental group, as evidenced by post-test averages of 19.79 and 16.03, respectively. Further analysis with ANCOVA showed a significant effect of the instructional treatment on post-test scores after controlling for pre-test differences (F(1, 73) = 9.066, p = 0.004, partial η² = 0.110). The findings suggest that edutourism-based learning, which emphasizes direct interaction with nature, observation activities, and student-designed solutions to environmental problems, effectively promotes student ecological awareness. This study contributes to contextual and constructivist learning literature by demonstrating the role of authentic, ecology-based learning experiences in science education. However, implementation challenges related to access, logistics, and limited intervention duration remain. Future research should explore longitudinal and interdisciplinary approaches, including technology-supported alternatives, to overcome contextual constraints. Keywords: environmental education, educational tourism, ecological awareness, integration, science module.